2020
DOI: 10.1182/bloodadvances.2020002309
|View full text |Cite
|
Sign up to set email alerts
|

The S enantiomer of 2-hydroxyglutarate increases central memory CD8 populations and improves CAR-T therapy outcome

Abstract: Cancer immunotherapy is advancing rapidly and gene-modified T cells expressing chimeric antigen receptors (CARs) show particular promise. A challenge of CAR-T cell therapy is that the ex vivo–generated CAR-T cells become exhausted during expansion in culture, and do not persist when transferred back to patients. It has become clear that naive and memory CD8 T cells perform better than the total CD8 T-cell populations in CAR-T immunotherapy because of better expansion, antitumor activity, and persistence, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…Because the epigenetic imprinting of a memory phenotype could be achieved through small molecule inhibition of MPC in vitro , we saw an opportunity to harness the memory-inducing effect of MPC inhibition for CAR T cell manufacturing while avoiding T cell functional collapse in the nutrient-deprived tumor microenvironment upon systemic MPC inhibition. Indeed, epigenetic intervention with small molecules or metabolites during CAR T cell manufacturing is an emerging strategy to either prevent loss of CAR expression and exhaustion ( Kong et al., 2021 ) or induce a memory phenotype ( Foskolou et al., 2020 ). While it also efficiently induces memory differentiation, interfering with glycolysis to optimize ACT has proven to negatively affect CAR T cell yield ( Klein Geltink et al., 2020 ; Sukumar et al., 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Because the epigenetic imprinting of a memory phenotype could be achieved through small molecule inhibition of MPC in vitro , we saw an opportunity to harness the memory-inducing effect of MPC inhibition for CAR T cell manufacturing while avoiding T cell functional collapse in the nutrient-deprived tumor microenvironment upon systemic MPC inhibition. Indeed, epigenetic intervention with small molecules or metabolites during CAR T cell manufacturing is an emerging strategy to either prevent loss of CAR expression and exhaustion ( Kong et al., 2021 ) or induce a memory phenotype ( Foskolou et al., 2020 ). While it also efficiently induces memory differentiation, interfering with glycolysis to optimize ACT has proven to negatively affect CAR T cell yield ( Klein Geltink et al., 2020 ; Sukumar et al., 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, within the TME, it has been demonstrated that upregulation of HIF-1a increases the production of the S enantiomer of 2-hydroxyglutarate (S-2HG), which is involved in driving epigenetic remodeling to enhance IL-2 production in antitumor T cells [ 129 ]. Recent studies suggest that culturing antitumor T cells with S-2HG ex vivo increases the central memory CD8 + population and enhances their antitumor efficacy [ 129 , 130 ].…”
Section: Epigeneticsmentioning
confidence: 99%
“…Expanding CAR-T cells in the presence of S-2HG yields increased proportions of central memory cells, regardless of the co-stimulatory domain included in the CAR design. Importantly, the in vitro cytotoxic activity and cytokine production of S-2HG treated CAR-T cells was not impaired, and in a mouse xenograft model, CAR-T cells treated with S-2HG display enhanced anti-tumour activity and reduced tumour progression [ 58 ].…”
Section: Current Metabolic Conditioning Of Car-t Cellsmentioning
confidence: 99%